Full Waveform Analysis for Long-Range 3D Imaging Laser Radar. (18th August 2010) - Wallace Wallace, Andrew M. Andrew M.; Ye Ye, Jing Jing; Krichel Krichel, Nils J. Nils J.; McCarthy McCarthy, Aongus Aongus; Collins Collins, Robert J. Robert J.; Buller Buller, Gerald S. Gerald S.
Abstract : The new generation of 3D imaging systems based on laser radar (ladar) offers significant advantages in defense and security applications. In particular, it is possible to retrieve 3D shape information directly from the scene and separate a target from background or foreground clutter by extracting a narrow depth range from the field of view by range gating, either in the sensor or by postprocessing. We discuss and demonstrate the applicability of full-waveform ladar to produce multilayer 3D imagery, in which each pixel produces a complex temporal response that describes the scene structure. Such complexity caused by multiple and distributed reflection arises in many relevant scenarios, for example in viewing partially occluded targets, through semitransparent materials (e.g., windows) and through distributed reflective media such as foliage. We demonstrate our methodology on 3D image data acquired by a scanning time-of-flight system, developed in our own laboratories, which uses the time-correlated single-photon counting technique.